The role of responsive heterogeneity in sub-Saharan smallholder farming sustainability: socio-economic and biophysical determinants of mineral and organic fertilizers used in South Western Burkina Faso - Thiombiano, Boundia Alexandre; Le, Quang Bao; Ouédraogo, Dénis (Taylor & Francis, 2023)
Sustainable soil nutrient management (SNM) is important for improving soil resources and food security in sub-Saharan African countries. Inherent livelihood diversity may lead to differences in household behavior in the adoption of SNM practices, thus challenging policy interventions uniformly implemented. This study aims at exploring the responsive heterogeneity in household behavior in the adoption of fertilizer use by farmers. Determinants of fertilizer uses were analyzed across different farm types. These farm types were identified from farm-household data collected in six villages in the South Western of Burkina Faso using the Sustainable Livelihood Framework. Using multilinear and binary logistic models, determinants of mineral, organic and combined mineral-organic fertilizer uses were analyzed. The results revealed that the determinants of SMN adoption include not only common determinants to whole sampled population (income, household size, access to roads and cereal areas), but also specific determinants to farm types (small ruminants, animal power, educational level and access to agro-training). This finding suggests that policy interventions will not be effective if the responsive heterogeneity in SNM adoption behavior is not taken into account. The study recommends the use of the presented framework, as an approach, to identify functional farm types to be considered in SNM policies.